Model of Implementation of Islamic Communication Values in Public Services: A Participatory Study at Haji Hospital Medan - Hasrimy, Muhammad Faisal; Abdullah, Abdullah (Program Pascasarjana UIN Sumatera Utara, 2025)
Effective communication is a fundamental element in public service bureaucracies, especially in the healthcare sector, which is complex, dynamic, and directly impacts human life. However, many public institutions including government hospitals continue to face serious communication problems, such as misinformation, lack of empathy, and rigid bureaucratic interaction styles. This study aims to develop an implementable and contextual model of Islamic communication values within the bureaucratic system of public health services, using a participatory approach at RS Haji Medan, a government hospital with a strong Islamic identity. The research adopts a qualitative applied method with a Participatory Action Research (PAR) framework, involving hospital managers, medical staff, administrative personnel, and patients as active collaborators in diagnosing problems, formulating values, and testing the model. Findings show that while values such as shidq (truthfulness) and amanah (trustworthiness) are relatively applied, others like tabligh (clarity), fathanah (communicative intelligence), and ihsan (excellence with empathy) remain inconsistently practiced and depend largely on individual initiative. A five-component model was developed: (1) core Islamic values, (2) SOP for Islamic communication, (3) ethical communication guidelines, (4) internal training programs, and (5) value-based feedback systems. The pilot implementation in outpatient and emergency units demonstrated improvement in patient-staff communication, increased staff confidence, and enhanced institutional accountability. This study concludes that Islamic communication values can be translated into practical tools and procedures to humanize public service communication, especially in healthcare bureaucracies. The model is recommended for replication in similar institutions across Indonesia seeking to integrate spiritual and ethical dimensions into public service delivery.